The boundedness of commutator of Riesz transform associated with Schrödinger operators on a Hardy space - Canqin Tang; Chuanmei Bi (Journal of Function Spaces and Applications)
In this paper, we study the boundedness of commutator [b,T] of Riesz transform associated with Schrödinger operator and b is BMO type function, note that the kernel of T has no smoothness, and the boundedness from Hb1(Rn)→L1(Rn) is obtained.